Analisis Line Balancing pada Proses Produksi Style Order Long Pants - Sugiyarto, Sugiyarto; Yulianto, Bambang; Mirnawati, Silvia Septi (Akademi Komunitas Industri Tekstil Dan Produk Tekstil Surakarta, 2021)
Line balancing is an assignment of a number of jobs into interconnected work stations in one production line. PT PB Tbk. is a company engaged in garment industry producing apparel. One of the products is long pants, there are 137 work elements which are divided into 4 work stations, where each work element consists of 1 operator. During production process, unbalance workload problems often occur such as a lot of idle time for some operatorsand overload for other operators. Based on this issue, it is necessary to recalculate the number of work stations and distribute the workload to avoid excessive idle time so that work can be more effective and efficient. One way to overcome this problem is applying line balancing method, with the aim that implementation of this line balancing method may achieve optimal results and each work station works effectively and has maximum work efficiency. The results of this study showed that there were additional work stations from 4 to 57, however there were adjustments to the workload. Keywords: line balancing, work station, bottleneck, work elements, efficiency